Endoscopic endonasal resection of an epidermoid cyst in the cavernous sinus: A case report and literature review - Wu, Yinzi; Li, Zhimin; Gao, Jun; Yao, Yong; Wang, Renzhi; Bao, Xinjie (Frontiers in Oncology, 2022)
Background Epidermoid cysts of cavernous sinus (CS) are rare congenital neoplasms of the central nervous system. In previous literature reports, the treatment for CS epidermoid cysts was mainly microsurgical resection, and the surgical methods included simple microsurgery and endoscope-assisted microsurgery. The present case report demonstrates the first case of complete resection of a CS epidermoid cyst by a simple endoscopic endonasal transcavernous (EET) approach. Case presentation A 54-year-old woman presented with chronic persistent headaches and occasional syncope. Brain MRI demonstrated a space-occupying lesion of the left CS, and digital substruction angiography (DSA) showed a small aneurysm at the beginning of the left ophthalmic artery. Thrombotic therapy of carotid–ophthalmic aneurysms was performed first, and the patient underwent resection of the CS lesion secondary. Considering the location of the lesion and the neuroendoscopy technology and experience of the doctor, we made bold innovations and used an EET approach to achieve complete resection of the lesion. The postoperative pathological results were consistent with the characteristics of epidermoid cyst. During the 1-year follow up, the patient showed no apparent signs of recurrence on head MRI. Conclusion Epidermoid cyst of cavernous sinus is a rare benign occupying lesion in cavernous sinus. Reviewing the previous literature, the main treatment is microneurosurgery, and neuroendoscopy is only used as an auxiliary equipment. We present the first case of complete endoscopic resection of CS epidermoid cyst by EET approach according to CARE guidelines, aiming to share the new surgical plan for CS epidermoid cyst and provide more surgical options for this disease for neurosurgery colleagues.